Multimodal Treatment of Bone Metastasis—A Surgical Perspective - Soeharno, Henry; Povegliano, Lorenzo; Choong, Peter F. (Frontiers in Endocrinology, 2018)
Over the past decades there has been an increase in the incidence of cancer worldwide. With the advancement in treatment, patient survival has improved in tandem with the increasing incidence. This, together with the availability of advanced modern diagnostic modalities, has resulted in more cases of metastatic bone disease being identified. Bone metastasis is an ongoing problem and has significant morbidity implications for patients affected. Multimodal treatment strategies are required in dealing with metastatic bone disease, which include both surgical and non-surgical treatment options. In the multidisciplinary team, orthopedic surgeons play an important role in improving the quality of life of cancer patients. Surgical intervention in this setting is aimed at pain relief, restoration of function and improvement in functional independence. In selected cases with resectable solitary metastasis, surgical treatment may be curative. With the advancement of surgical technique and improvement in implant design and manufacture, a vast array of surgical options are available in the modern orthopedic arena. In the majority of cases, limb salvage procedures have become the standard of care in the treatment of metastatic bone disease. Non-surgical adjuvant treatment also contributes significantly to the improvement of cancer patient care. A multidisciplinary approach in this setting is of paramount importance.